PSYCHOLOGICAL CHARACTERISTICS OF WORKING WITH INCARCERATED INDIVIDUALS - Zafar Turdiyev (Modern World Education: New Age Problems – New solutions, 2026)
This article provides a scientific-theoretical analysis of the psychological characteristics of working with incarcerated individuals. It examines the mental state of prisoners, their emotional instability, difficulties in social adaptation, deficiencies in communicative competence, and problems with self-assessment. The study draws upon Erik Erikson’s theory of psychosocial development, John Bowlby’s attachment theory, and Edwin H. Sutherland’s differential association theory to analyze the social-psychological features of prisoners. Additionally, the effectiveness of individual and group psychological support, motivational programs, and the development of social skills for successful reintegration into society is discussed.